Activated Carbon of Oil Palm Empty Fruit Bunch (EFB); Core and Shaggy. (2016) - Osman, N.B.; Shamsuddin, N.; Uemura, Y.
Abstract: Oil palm empty fruit bunches activated carbon of different parts (shaggy and core) were characterized as to convert waste of oil palm-based into value added products. Conventional step processes of physical activation were performed where activation was undertaken after the pyrolysis process (carbonization-activation process). The pyrolysis temperatures applied were 400, 450, and 500°C in inert condition under nitrogen flow. For the activation process, 600, 700, and 800°C with the presence of 15%, 60%, and 100% CO2 and holding time of 30, 60, and 120 minutes were applied. Results showed that activation temperature, CO2 percentage and holding time did dictate the changes of activated carbon yield, carbon content, and textural properties of the activated carbon core and shaggy EFB produces. The highest yield of activated carbon was obtained from 700°C (middle temperature), 60% CO2 (middle percentage), and 30 mins holding time (shortest). However, the highest carbon content was detected from 600°C, 60% CO2, and 60 mins of activated carbon core EFB. The size of pore determined prove that the three parameter do not correlate with each other as the bigger pore diameter was derived from 700°C, 60% of CO2, and 60 mins holding time. Hence, the results revealed that there are differences of activated carbon properties when we separate EFB part into its core and shaggy.